2012
DOI: 10.1111/j.1538-7836.2012.04707.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance and risk of venous thromboembolism: results of a population‐based cohort study

Abstract: To cite this article: van Schouwenburg IM, Mahmoodi BK, Veeger NJGM, Bakker SJL, Kluin-Nelemans HC, Meijer K, Gansevoort RT. Insulin resistance and risk of venous thromboembolism: results of a population-based cohort study. J Thromb Haemost 2012; 10: 1012-8.Summary. Background: Obesity is an established risk factor for venous thromboembolism (VTE), but it is uncertain how this is mediated. Insulin resistance has a central role in the pathophysiology of the metabolic effects of obesity. Objective: We aimed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 37 publications
4
28
0
Order By: Relevance
“…The prevalence of insulin resistance is increased in obese individuals [42], and improves with weight loss [43][44][45]. Schouwenburg et al [46] showed that insulin resistance was not associated with the risk of VTE after adjustment for BMI in a population-based cohort. In contrast, a recent report from the Iowa Women's Health Study [18] showed an association between diabetes and VTE in women, even after adjustment for BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of insulin resistance is increased in obese individuals [42], and improves with weight loss [43][44][45]. Schouwenburg et al [46] showed that insulin resistance was not associated with the risk of VTE after adjustment for BMI in a population-based cohort. In contrast, a recent report from the Iowa Women's Health Study [18] showed an association between diabetes and VTE in women, even after adjustment for BMI.…”
Section: Discussionmentioning
confidence: 99%
“…It is, thus, legitimate to ask whether IR itself is a risk factor for VTE. Unfortunately, little information is available and only one large prospective population-based cohort study specifically addressed this issue, showing that individuals with higher IR scores had an increased risk of unprovoked VTE, which was independent of several related risk factors, but not BMI (Van Schouwenburg et al 2012).…”
Section: Insulin Resistance As a Predictor Of Venous Thromboembolism mentioning
confidence: 99%
“…This process ultimately leads to a prothrombotic tendency by enhancing coagulation while inhibiting fibrinolysis [78,79], which in some cases can contribute to the pathogenesis of VTE associated with abdominal obesity [32]. Indeed, insulin resistance has been reported to increase the risk of VTE in a BMI-dependent manner [80].…”
Section: In Relation To Inflammation and Insulin Resistancementioning
confidence: 99%